Silk Hydrogels of Tunable Structure and Viscoelastic Properties Using Different Chronological Orders of Genipin and Physical Cross- Linking - Elliott, Winston H. (ACS Appl Mater Interfaces, 2015)
Catering the hydrogel manufacturing process toward defined viscoelastic properties for intended biomedical use is important to hydrogel scaffolding function and cell differentiation. Silk fibroin hydrogels may undergo “physical” cross-linking through β-sheet crystallization during high pressure carbon dioxide treatment, or covalent “chemical” cross-linking by genipin. We demonstrate here that time-dependent mechanical properties are tunable in silk fibroin hydrogels by altering the chronological order of genipin cross-linking with β-sheet formation. Genipin cross-linking before β-sheet formation affects gelation mechanics through increased molecular weight, affecting gel morphology, and decreasing stiffness response. Alternately, genipin cross-linking after gelation anchored amorphous regions of the protein chain, and increasing stiffness. These differences are highlighted and validated through large amplitude oscillatory strain near physiologic levels, after incorporation of material characterization at molecular and micron length scales.